Microwave-assisted syntheses of BODIPY–sugar conjugates through click chemistry and conjugate assembly into liposomes. (7th April 2016) - Yalagala, Ravi Shekar; Mazinani, Sina Atrin; Maddalena, Lucas A.; Stuart, Jeffrey A.; Yan, Fengyang; Yan, Hongbin
Highlights: Conjugation of glycans with BODIPY via click chemistry under microwave heating. Assembly of conjugate into liposomes. Shift of BODIPY fluorescence from green to red in the bilayer. Graphical Abstract: Abstract: BODIPY fluorophores bearing azide or terminal alkyne functions were conjugated with glycans modified with terminal alkyne or azido through the Cu(I)-catalyzed 1, 3-dipolar azide–alkyne cycloaddition (CuAAC) chemistry under microwave heating while these reactions did not proceed when heated in an oil-bath. The BODIPY–glycan conjugate product8a undergoes self-assembly into liposomes when hydrated. Formation of liposomes was confirmed by both bright field and confocal microscopy. Fluorescent emission within the liposome was shifted from green to red due to effective high concentrations.